Fine-tuning of regulatory T cells is indispensable for the metabolic steatosis-related hepatocellular carcinoma: A review - Riaz, Farooq; Wei, Ping; Pan, Fan (Frontiers in Cell and Developmental Biology, 2022)
The majority of chronic hepatic diseases are caused by nutritional imbalance. These nutritional inequities include excessive intake of alcohol and fat, which causes alcoholic liver disease (ALD) and non-alcoholic fatty liver disease (NAFLD), respectively. The pathogenesis of hepatic diseases is mainly dependent on oxidative stress, autophagy, DNA damage, and gut microbiota and their metabolites. These factors influence the normal physiology of the liver and impact the hepatic microenvironment. The hepatic microenvironment contains several immune cells and inflammatory cytokines which interact with each other and contribute to the progression of chronic hepatic diseases. Among these immune cells, Foxp3+ CD4+ regulatory T cells (Tregs) are the crucial subset of CD4+ T cells that create an immunosuppressive environment. This review emphasizes the function of Tregs in the pathogenesis of ALD and NAFLD and their role in the progression of NAFLD-associated hepatocellular carcinoma (HCC). Briefly, Tregs establish an immunosuppressive landscape in the liver by interacting with the innate immune cells and gut microbiota and their metabolites. Meanwhile, with the advancement of steatosis, these Tregs inhibit the proliferation, activation and functions of other cytotoxic T cells and support the progression of simple steatosis to HCC. Briefly, it can be suggested that targeting Tregs can act as a favourable prognostic indicator by modulating steatosis and insulin resistance during the pathogenesis of hepatic steatosis and NAFLD-associated HCC.